2023
DOI: 10.3390/sports11020045
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intake in NCAA Division 1 Soccer Players: Assessment of Daily Amounts, Distribution Patterns, and Leucine Levels as a Quality Indicator

Abstract: Dietary protein is required to support recovery and adaptation following exercise training. While prior research demonstrates that many athletes meet total daily protein needs, intake seems to be predominantly skewed toward the evening meal. An even distribution of protein doses of ≥0.24 g/kg BW consumed throughout the course of a day is theorized to confer greater skeletal muscle anabolism outcomes compared to a skewed pattern of intake. Protein quality is also an important dietary consideration for athletes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…Morning snacks provided insufficient amounts of protein, while the main intake came from dinner and after dinner snacks. Consistent with our findings, Kwon et al found that dinner was the highest protein containing meal, whose intake was uneven distributed across meals, in both male and female soccer players (42).Even though the low number of subjects involved, the present results suggest that athletes adequately met total protein requirements, but food sources and timing should be better emphasized.…”
Section: Discussionsupporting
confidence: 91%
“…Morning snacks provided insufficient amounts of protein, while the main intake came from dinner and after dinner snacks. Consistent with our findings, Kwon et al found that dinner was the highest protein containing meal, whose intake was uneven distributed across meals, in both male and female soccer players (42).Even though the low number of subjects involved, the present results suggest that athletes adequately met total protein requirements, but food sources and timing should be better emphasized.…”
Section: Discussionsupporting
confidence: 91%
“…So it can be concluded that there is a relationship between the amount of breakfast eaten and anemia status. The results of this study are in line with (Afritayeni 2019) where there is a relationship between the amount of food and hemoglobin levels in adolescent girls at SMP Negeri 20 Pekabnbaru (p = 0,028) (Kwon et al, 2023). Table 7 shows that in the analysis of the relationship between food frequency and anemia status of 32 respondents with a frequency of eating once a day, there were 2 respondents (14.3%) who had anemia and 31 respondents out of 13 respondents (35.7%) who had anemia in the <3 times a week category.…”
Section: A Bivariate Analysissupporting
confidence: 90%
“…As a meal plan, nutrition is important because it can help you perform better and consume more macro, micro, and fluid nutrients. As indicated by Kwon et al, (2023), volleyball athletes must pay close attention to their nutrition on match days, during training, body composition, stressful environments, cultural diversity, and dietary considerations, as well as food supplements.…”
Section: Resultsmentioning
confidence: 99%